2009
DOI: 10.5053/ejobios.2009.3.0.15
|View full text |Cite
|
Sign up to set email alerts
|

The effect of regular intake of Terminalia chebula on oxidative stress in mice originated from Salmonella typhimurium

Abstract: Typhoid is endemic and in most developing countries remains a public health problem. Due to an increasing resistance to antibiotics and the limited scope of the vaccine the requirement is to explore the efficacy of natural plant products in the treatment of this disease. In this study we have evaluated the aqueous extract of Terminalia chebula in connection with the oxidative stress generated in Swiss albino mice by Salmonella typhimurium. Mice pretreated through the oral route with the water extract of T. che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 32 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…chebula exhibited antibacterial activity against a number of both Gram-positive and Gram-negative human pathogenic bacteria [47][48][49] . Ethanedioic acid and ellagic acid isolated from butanol fraction of T. chebula fruit extract had strong antibacterial activity against intestinal bacteria, Clostridium perfingens and Escherichia coli [50] .…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…chebula exhibited antibacterial activity against a number of both Gram-positive and Gram-negative human pathogenic bacteria [47][48][49] . Ethanedioic acid and ellagic acid isolated from butanol fraction of T. chebula fruit extract had strong antibacterial activity against intestinal bacteria, Clostridium perfingens and Escherichia coli [50] .…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Aqueous, ethanol, and ethyl acetate extracts of T. chebula fruits also demonstrated no cellular toxicity on sheep erythrocytes as well as acute oral toxic effects on rats at recommended and higher doses [48,91,92] . Besides, hydroalcoholic extract of T. chebula fruits demonstrated cytochrome P-450 inhibition potential in rats [93] .…”
Section: Safety Evaluationmentioning
confidence: 99%
“…It has a global distribution and is a worldwide problem as described by Khan et al [66][67][68][69][70] Typhoid can be treated by using antibiotics. 66,70 Vaccination 66,70 and herbal drugs [66][67][68][69][71][72][73][74][75][76] also showed interesting results. 64 A number of plants have been reviewed by this author for their medicinal assessment.…”
Section: Dna Vaccine Against Typhoidmentioning
confidence: 99%
“…62 Another study revealed antibacterial activity of extract from T. chebula fruit against E. coli, P. aeruginosa, shigella flexineria, and S. aureus 63 . Its extracts demonstrated no cellular toxicity at even higher doses thus proving it to be a safe drug 64 .…”
Section: Crataeva Nurvala (Varun)mentioning
confidence: 98%